3D photothermal reconstruction of subsurface defects in notched multidirectional CFRP laminates due to tensile fatigue loading. (October 2022) - Gahleitner, L.; Thummerer, G.; Reitinger, B.; Meirer, K.; Mayr, G.
Abstract: This paper presents results from 3D photothermal reconstruction of real subsurface defects in carbon fiber-reinforced polymers using the virtual wave concept. We apply pulsed thermography during and after interrupted fatigue loading in tensile-tensile configuration for notched multidirectional laminates. In addition, we discuss the influence of the ambient conditions from in-situ photothermal testing on the virtual wave signal. The results obtained from 3D photothermal reconstruction are directly compared with those obtained from laser ultrasound testing. To summarize, we demonstrate a practicable and fast 3D photothermal evaluation of subsurface defect evolution utilizing the virtual wave concept.